2021
DOI: 10.3389/fpsyt.2021.761321
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition in Skin Picking Disorder and Trichotillomania

Abstract: Objective: Excessive calorie intake constitutes a global public health concern, due to its associated range of untoward outcomes. Impulsivity and compulsivity have been linked to dietary intake. However, nothing is known about dietary intake and body-focused repetitive behaviors, despite their classification as obsessive-compulsive related conditions, and high co-morbidity with impulsive and compulsive conditions.Methods: One hundred and ninety six adults with trichotillomania or skin picking disorder were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
1
0
2
Order By: Relevance
“…[8] Zaczerpnięta od imienia długowłosej bohaterki baśni braci Grimm nazwa zespołu Roszpunki odnosi się do szczególnej postaci trichobezoaru, w którym jego ogon rozciąga się do jelit i może powodować ich niedrożność. [9] Trichotillomania przyczynia się do znacznego cierpienia i upośledzenia funkcjonowania w życiu społecznym zawodowym. [1] Mimo że trichotillomania znacząco wpływa na jakość życia, większość chorych (około 65% lub więcej) nigdy nie szuka leczenia.…”
Section: Wstępunclassified
See 1 more Smart Citation
“…[8] Zaczerpnięta od imienia długowłosej bohaterki baśni braci Grimm nazwa zespołu Roszpunki odnosi się do szczególnej postaci trichobezoaru, w którym jego ogon rozciąga się do jelit i może powodować ich niedrożność. [9] Trichotillomania przyczynia się do znacznego cierpienia i upośledzenia funkcjonowania w życiu społecznym zawodowym. [1] Mimo że trichotillomania znacząco wpływa na jakość życia, większość chorych (około 65% lub więcej) nigdy nie szuka leczenia.…”
Section: Wstępunclassified
“…Modyfikacja diety mogłaby być potencjalnie kolejną użyteczną interwencją w leczeniu. [9] Istotnym aspektem jest także leczenie TTM występującej we śnie; przeprowadzono m.in. badanie dotyczące wpływu higieny snu i melatoniny na nasilanie objawów, lecz kwestia ta wymaga dalszych analiz.…”
Section: Leczenieunclassified
“…In overweight people, increased consumption of SSBs was associated with an increased incidence of a diagnosis of depression [ 263 ]. The results of studies on repetitive body-centred behaviour found that high-sugar consumption was associated with greater impulsivity without planning, whereas diets high in both saturated fat and sugar were associated with greater motor impulsiveness among study participants [ 264 ]. Large amounts of added sugar in food induced greater sensitivity to delays, greater preference for larger size, and increased size sensitivity [ 265 ], according to an earlier study in rats in the impulsive choice task [ 266 ].…”
Section: Hsd Evokes Behavioural Predictors Of Drug Of Abusementioning
confidence: 99%